2019
DOI: 10.1016/j.jmaa.2019.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Values of harmonic weak Maass forms on Hecke orbits

Abstract: Let q := e 2πiz , where z ∈ H. For an even integer k, let f (z) := q h ∞ m=1 (1 − q m ) c(m) be a meromorphic modular form of weight k on Γ 0 (N ). For a positive integer m, let T m be the mth Hecke operator and D be a divisor of a modular curve with level N . Both subjects, the exponents c(m) of a modular form and the distribution of the points in the support of T m .D, have been widely investigated.When the level N is one, Bruinier, Kohnen, and Ono obtained, in terms of the values of jinvariant function, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The divisor lifting involving the generating function of J n for a weight k meromorphic modular form to a weight 2 meromorphic modular form, as described in (1.4), was generalized by Bringmann et al [3,Theorem 1.3] and Choi, Lee, and Lim [6,Theorem 1.1]. They extended this lifting to meromorphic modular forms of arbitrary level with respect to Niebur-Poincaré harmonic weak Maass functions, resulting in the holomorphic part of the Fourier expansion of a weight 2 polar harmonic weak Maass form.…”
Section: Introductionmentioning
confidence: 99%
“…The divisor lifting involving the generating function of J n for a weight k meromorphic modular form to a weight 2 meromorphic modular form, as described in (1.4), was generalized by Bringmann et al [3,Theorem 1.3] and Choi, Lee, and Lim [6,Theorem 1.1]. They extended this lifting to meromorphic modular forms of arbitrary level with respect to Niebur-Poincaré harmonic weak Maass functions, resulting in the holomorphic part of the Fourier expansion of a weight 2 polar harmonic weak Maass form.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been generalized by Bringmann et al [3,Theorem 1.3] and Choi, Lee and Lim [6,Theorem 1.1] to Niebur-Poincaré harmonic weak Maass functions J N,n (τ ) of arbitrary level N . For every point z ∈ H, we define…”
Section: Statement Of Resultsmentioning
confidence: 79%
“…In [10], Bruinier, Kohnen and Ono showed that the logarithmic derivative of a meromorphic modular form f on SL 2 (Z) is expressible in terms of the values of Faber polynomials of j(τ ) at points τ in the divisor of f , which generalizes the denominator formula. These results have been generalized by Bringmann et al [9] and Choi, Lee and Lim [16] to Niebur-Poincaré harmonic weak Maass functions of arbitrary level N . They proved that the logarithmic derivative of a meromorphic modular form for Γ 0 (N ) is explicitly described in terms of the values of Niebur-Poincaré series at its divisors in H. In this paper, we verify that this logarithmic differential operator defined on the multiplicative group of meromorphic modular forms for Γ 0 (N ) with a unitary multiplier system (possibly of infinite order) is also Hecke equivariant under the extension of Guerzhoy's multiplicative Hecke operator and the Hecke operator on the weight 2 meromorphic modular forms for Γ 0 (N ).…”
Section: Introductionmentioning
confidence: 68%
“…where F N is the fundamental domain of Γ 0 (N ) and 1/e N,z is the cardinality of Γ 0 (N ) z /{±1} for each z ∈ H, where Γ 0 (N ) z denotes the stabilizer of z in Γ 0 (N ). Bringmann et al [9] and Choi, Lee, and Lim [16] have extended these results to Niebur-Poincaré harmonic weak Maass functions J N,n of arbitrary level N by proving that the logarithmic derivative of a meromorphic modular form for Γ 0 (N ) is described explicitly in terms of the values of J N,n at its divisors in H. In [20, Theorem 2.1], the authors showed that the logarithmic derivative of a meromorphic modular form for Γ 0 (N ) can be expressed explicitly in terms of the values of weakly holomorphic modular functions. Let M !…”
Section: Preliminariesmentioning
confidence: 97%